An open-label, dose-finding study of the combination of satraplatin and gemcitabine in patients with advanced solid tumors - Donato Di Paola, Eugenio; Alonso, Silvia; Giuliani, Rosa; Calabrò, Fabio; D'Alessio, Antonietta; Regine, Giovanni; Cerbone, Linda; Bianchi, Laura; Mancuso, Andrea; Sperka, Sabine; Rozencweig, Marcel; Sternberg, Cora N. (Frontiers in Oncology, 2012)
Purpose: Satraplatin is a third generation oral platinum, which has demonstrated antitumor activity. The aim of this phase I study was to determine the maximum tolerated dose (MTD) of the combination of satraplatin and gemcitabine in patients previously treated with chemotherapy and in patients without prior chemotherapy. Patients and Methods: Two separate MTDs were planned in two different patient groups (those with and without prior chemotherapy treatment). Dose escalations were planned in cohorts of three patients. Tumor measurements were obtained every two cycles. Assessment of response was performed according to Response Evaluation Criteria in Solid Tumors (RECIST criteria v.1.0). Results: Thirty subjects were enrolled. A MTD of gemcitabine 1000 mg/m2 days 1 and 8 plus satraplatin 60 mg/m2 days 1–3, every 21 days was determined in the prior chemotherapy group. No MTD could be determined for the no prior chemotherapy group treated with this schedule. Five patients completed 12 treatment cycles; 22 serious adverse events (SAE) were observed. Although not an entry criteria, overall confirmed response was observed in 17 (24%) evaluable patients (complete response, CR = 1 and partial response, PR = 3) and in 3/7 (43%) patients with measure prostate cancer lesions. Conclusions: In this phase Ib study, the combination of satraplatin and gemcitabine demonstrated to be safe and efficacious in particular in patients with prostate cancer.